Fatores determinantes ao ataque do percevejo-das-gramíneas e de lagartas desfolhadoras em pastagens no Município de Alto Alegre, Roraima - Silva, Regina Oliveira da (2018)
Among the several factors that contribute to the degradation of pastures, is the occurrence of insect pests. The main species observed to cause damage in pastures in Roraima and that contribute to the degradation are the grasshopper Blissus pulchellus (Hemiptera: Blissidae) and the defoliation caterpillars. The objective of this work was to identify the climatic and biotic factors that affect the grasshopper population and the defoliant caterpillars Mocis latipes and Spodoptera frugiperda in pastures in the municipality of Alto Alegre, Roraima. This study was conducted in three pasture areas in the municipality of Alto Alegre, RR, with attack of B. pulchellus and leafhopper caterpillars. Area 1 has about 60 ha of Uroclhoa brizantha cv. Marandu, area 2 with Uroclhoa brizantha cv. Marandu and area 3 with 10 ha of Panicum maximum cv. Mombasa. This study was carried out from June 2016 to June 2018. A population density survey of insect pests and natural enemies was carried out. The samples were placed in plastic bags and sent to Embrapa Roraima Laboratory of Entomology, where they were counted on bedbugs, caterpillars and natural enemies and later placed in a container with 70% alcohol. The analyzes of climatic variables were obtained from the National Institute of Meteorology – INMET. Samples of grasses for qualitative assessment of pastures were collected, bagged, identified and sent to the Natural Resources Nucleus - NUREN, for the determination of crude protein - CP, neutral detergent fiber - FDN and acid detergent fiber - FDA, months of July and December of 2017, characterizing rainy and dry season. The management data collections were measured plant height, area temperature and below the plant, during the months of August 2017 to August 2018. Population densities of B. pulchellus, leafhoppers M. latipes and S. frugiperda of the major natural enemies were submitted to analysis of variance using the ANOVA procedure of the program BIOSTAT 5.0 (2007). The analyzes of the interrelation between population density and climatic factors and pasture management were submitted to Pearson correlation. ANOVA was performed to evaluate the relationship between population density of B. pulchellus and leafhopper caterpillars and pasture quality in relation to study areas in rainy and dry periods. There was no correlation between the population density of B. pulchellus and climatic variables and pasture management. There was a positive correlation between precipitation and the population density of the M. latipes and S. frugiperda caterpillar. There was a positive correlation between the natural enemies of the Coleoptera Order and the M. latipes caterpillar. There was a positive correlation between pasture quality and rainy and dry season. In view of the obtained results, it is explicit that there is a need to carry out new research involving the factors associated with the population dynamics of the B. pulchellus bed bug and the leafhopper caterpillars for longer periods, for a greater observation of the factors that imply the occurrence of these pests.